Performance of High-Damping Rubber Bearings for Seismic Isolation – Case Study of Nayumi Sam Tower Malang Apartment - Ibnu Pudji Raharjo; Yuyun Tajunnisa; Indra Komara; Geralda Nurry Arifa; Sungkono Sungkono; Dicky Imam Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The base-isolation system is a highly effective earthquake-resistance technique. Especially when the building is under soft soil, however, it is detrimental to the horizontal displacement control of the isolation layer and less effective in decreasing the seismic response of the superstructure. Rubber bearings with high damping can produce substantial hysteretic damping and exhibit a hardening effect at high-shear strains. The research investigates the Nayumi Sam Tower Malang apartment as a case study with 10 stories of reinforced concrete with a double system structure which is in a soft soil location. High-damping rubber bearings (HDRBs) is used as a parameter study to understand the alteration and give a recommendation. The seismic response of the building is evaluated, and the HRDB alternative systems is confirmed using ETABS. It is pointed out that the HRDBs system can reduce the impact of earthquakes by close to 25% with the smallest section of structural dimension. According to new regulation building in Indonesia, the precise values of test circumstances, such as compressive force, shear displacement, and frequency, are developed. The findings are thoroughly discussed, the applicability of HRDBs for seismic isolation of residential buildings is concluded. Building with HRDBs isolation implied to have lower base shear and inter-storey drift which improved the performance of the structure with less damage.